MODERN LABORATORY METHODS OF HELMINTHIC DISEASES - Umarova T. A.; Kudratova Z. E.; Xoshimov S. (Web of Journals Publishing, 2024)
Helminthic diseases- are the most common parasitic diseases of humans caused by various representatives of lower worms - helminths. The prevalence of helminthic diseases depends on natural and social factors. Of great importance are climatic conditions, such as soil and air temperature, precipitation, humidity, in which helminths, eggs, or larvae excreted in the feces.
Keywords: Helminthic diseases, larvae, eggs, food, parasitologic methods of research.